Essentials of corporate finance - Ross, Stephen A.; Jordan, Bradford D.; Westerfield, Randolph W. (The McGraw-Hill/Irwin series in finance, insurance, and real estate, 2011)
The three basic themes that emerge in this student text are an emphasis on working at an intuitive level, a unified valuation approach to corporate finance and a managerial focus emphasising the role of the financial manager as a decision maker